Revision of the genus Homa Distant (Hemiptera: Cicadellidae: Typhlocybinae) - Xu, Ye; Wang, Yi-Mei; Dmitriev, Dmitry A.; Dietrich, Christopher H.; Qin, Dao-Zheng (Zootaxa, 2022)
The leafhopper genus Homa Distant is revised. Four new species, H. osificata Xu, Dietrich & Qin sp. nov., H. oretinia Xu, Dietrich & Qin sp. nov., H. asilata Xu, Dietrich & Qin sp. nov., and H. algulata Xu, Dietrich & Qin sp. nov., are described from Thailand. H. haematoptilus (Kirkaldy) is redescribed based on specimens from the Oriental Region. All included species are illustrated and a key is provided to separate species for which males are known.